RCT of the effect of berryfruit polyphenolic cultivar extract in mild steroid-naive asthma: a cross-over, placebo-controlled study. Issue 3 (20th March 2017) - Power, Sharon; Williams, Mathew; Semprini, Alex; Munro, Claire; Caswell-Smith, Rachel; Pilcher, Janine; Holliday, Mark; Fingleton, James; Harper, Jacquie; Hurst, Roger; Weatherall, Mark; Beasley, Richard; et al.
Abstract : Objective: There is preclinical evidence that consumption of berryfruit extract may reduce chronic airways inflammation and modify airway remodelling in allergen-induced models of lung inflammation. We investigated the effect of berryfruit extract on the fractional expired nitric oxide (FeNO), a biomarker of eosinophilic airways inflammation, in adults with steroid-naïve asthma. Design: Randomised placebo-controlled cross-over double-blind trial. Setting: Single-centre community-based trial. Participants: 28 steroid-naïve mild asthmatics with Feno >40 ppb, of whom 25 completed both study interventions. Interventions: Participants were randomised to receive, according to the cross-over design, 100 mg berryfruit polyphenolic extract (BFPE) or placebo for 4 weeks, with a 4-week washout period between the interventions. Primary outcome measure: The primary outcome variable was FeNO at 4 weeks, analysed by a mixed linear model, with a random effect for participant and baseline FeNo as a covariate. Results: The mean (SD) natural logarithm transformed (ln) FeNO after 4 weeks of treatment for the BFPE and placebo groups was 4.28 (0.47) and 4.22 (0.47), respectively. The paired change from baseline mean (SD) BFPE minus placebo ln FeNO was −0.03 (0.39), N=25. The mixed linear model estimate, with baseline covariate adjustment, difference in ln FeNO, was −0.002 (95% CI −0.15 to 0.14), p=0.98. This is equivalent to a ratio of geometric mean FeNO of 1.0 (95% CI 0.86 to 1.15). Conclusions: In steroid-naïve participants with mild asthma and elevated FeNO, there was no effect of BFPE on FeNO, a biomarker of eosinophilic airways inflammation. Caution is required in the extrapolation of apparent benefit in murine models of lung eosinophilia to clinical efficacy in patients with asthma. Trial registration number: ANZCTR: 12613000451707 ; Results.